2013
DOI: 10.1182/blood-2013-04-495515
|View full text |Cite
|
Sign up to set email alerts
|

Effector T cells require fatty acid metabolism during murine graft-versus-host disease

Abstract: Key Points• T cells activated during GVHD increase their dependence upon fatty acid oxidation. • This dependence is not observed following acute activation or during normal immune reconstitution, suggesting novel therapeutic targets.Activated T cells require increased energy to proliferate and mediate effector functions, but the metabolic changes that occur in T cells following stimulation in vivo are poorly understood, particularly in the context of inflammation. We have previously shown that T cells activate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
178
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 127 publications
(186 citation statements)
references
References 31 publications
(46 reference statements)
8
178
0
Order By: Relevance
“…2A). This finding is consistent with increased glutamine-dependent anaplerosis, because we previously showed that total fatty acid uptake and oxidation increase in alloreactive T cells, excluding decreased uptake / utilization as an alternative explanation (Byersdorfer et al, 2013). In addition, among the 13 C-containing isotopomers of ribose, the molar enrichment of m2 species is significantly enhanced (Supplemental Fig.…”
Section: When Mice Receive [U-supporting
confidence: 76%
See 2 more Smart Citations
“…2A). This finding is consistent with increased glutamine-dependent anaplerosis, because we previously showed that total fatty acid uptake and oxidation increase in alloreactive T cells, excluding decreased uptake / utilization as an alternative explanation (Byersdorfer et al, 2013). In addition, among the 13 C-containing isotopomers of ribose, the molar enrichment of m2 species is significantly enhanced (Supplemental Fig.…”
Section: When Mice Receive [U-supporting
confidence: 76%
“…2B), the limited use of glutamine for fatty acid synthesis in alloreactive T cells is unlikely to result from an increase in reductive carboxylation. Together with recent data showing that alloreactive T cells actively import fatty acids from extracellular sources, our results suggest fatty acid uptake is used in preference to de novo synthesis (Byersdorfer et al, 2013).…”
Section: Anaplerosis Controls T Cell Function In Vivomentioning
confidence: 48%
See 1 more Smart Citation
“…Although memory T cells preferentially utilize FA metabolism (41,70), Teffs can also rely on FAO during GVHD (65). Increased FA uptake and FAO, and enhanced susceptibility to pharmacologic inhibition of FAO by etomoxir in WT donor T cells, suggest that PD-L1 provides a cell-intrinsic positive stimulus for FA metabolism in alloreactive T cells undergoing clonal expansion, which may further support T cell survival, extending in vitro studies by others using human T cells (45).…”
Section: Discussionmentioning
confidence: 67%
“…These include induction of aerobic glycolysis (61), OXPHOS (62), glutaminolysis, and increase in synthesis of biomolecules (63). T cell metabolism has also been shown to require lipid synthesis (64) or oxidation (65) and amino acid uptake (66). We (22) and others (67) have shown that GVHD results in high metabolic demands for Teffs, increasing their dependency on aerobic glycolysis.…”
Section: Discussionmentioning
confidence: 99%